Effect of thermal conditions on urban bioaerosol diffusion - Yuchen He (iJournals:International Journal of Software & Hardware Research in Engineering ISSN:2347-4890, 2025)
The diffusion characteristics of urban biogenic aerosols are closely related to public health risks. In this study, Beijing Zhongguancun, a densely populated area, was selected as the research object. A numerical model was established based on typical meteorological parameters to compare and analyze the effects of stable and unstable thermal conditions on the urban flow field and the diffusion of biogenic aerosols. The study found that in stable thermal conditions, the lateral and longitudinal diffusion of biogenic aerosols was relatively weak, and the range of high concentration areas near the ground was larger; while in unstable thermal conditions, the vertical turbulence enhancement promoted the rapid departure of aerosols from the near-ground activity area, the high concentration area was reduced, but the diffusion area was larger.